Study of Newly Synthesized Pyridinium-based Cationic Surfactants for Drug Interaction and Antibacterial Activity - Ali Jaan; Saqib Ali; Mohsin Javed; Ali Haider; Khurram Shahzad Munawar; Saja Abdulrahman Althobaiti; Mahboob ur Rehman (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Two pyridinium-based new cationic surfactants have been synthesized by the reaction of 2-methylpyridine and 3-methylpyridine with an alkyl halide (1-bromoctadecane) using dry toluene as a solvent to get the compounds, N-(n-octadecyl)-2-methylpyridinium bromide (A1) and N-(n-octadecyl)-3-methylpyridinium bromide (A2), respectively. The synthesized samples were characterized by using various spectroscopic techniques. The synthesized compounds showed a critical micelle concentration in a very low-value range (0.111 mM to 0.125 mM), proving the synthesized compounds' best surface-acting ability. Both compounds exhibited limited antibacterial activity across various bacterial strains, with inhibition zones ranging from 3 to 7 mm. The change in Gibb’s free energy (ΔG) was also calculated from their binding constant (Kb) for samples A1 (-10.0 kJ/mol) and A2 (-19.37 kJ/mol). The samples demonstrated spontaneous interactions with the drug molecules, which proved the efficient bioavailability of the drug due to the best incorporation of drug molecules with the aggregated monomers of surfactant molecules.